The first record of a paguroid shield (Decapoda, Anomura, Annuntidiogenidae) from the Miocene of Cyprus - Jonathan J.W. WALLAARD; René H.B. FRAAIJE; John W.M. JAGT; Adiël A. KLOMPMAKER; Barry W.M. VAN BAKEL (Geologija, 2020)
For the first time, a paguroid shield is recorded from upper Miocene reefal strata (Koronia Member, Pakhna Formation) that crop out along the northern margin of the Troodos Massif, north of the village of Mitsero, Cyprus. Described here as Paguristes joecollinsi sp. nov., it constitutes the first paguroid shield known from Miocene deposits. The paucity of Cenozoic paguroid shields can probably be linked to a collecting bias in view of their relatively small size; in addition, suitable gastropod shells and internal moulds of such should be screened for ‘hidden’ hermit crabs.